Digital holographic microscopy for microalgae biovolume assessment - Monaldi, Andrea Carolina (2015)
The relative amount of biomass in a body of water is one of the various indicators widely used in water quality evaluation. This implies complex tasks such as identification and characterization of microorganisms and measurement of their biovolume. Particularly, the latter is estimated by assuming simple geometrical shapes for the microorganism and by calculating its dimensions from images taken with a conventional microscope. In order to have a more precise and automatic method for biovolume evaluation, a hybrid methodology based on digital holographic microscopy and image processing is proposed. The whole volume of a specimen under study is obtained combining the phase contrast image of an off-axis hologram with the thickness-profile data of the specimen extracted from the cell silhouette. This technique has been used for determining the biovolume of Ceratium Hirundinella cells in water samples. The methodology proposed also shows that it is possible to estimate accurately an effective refractive index of the microorganism. Experimental results have shown that this technique is not only an efficient and fast alternative, but also suitable for automatizing the entire process.